2011
DOI: 10.1111/j.1528-1167.2011.03086.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereologic estimation of hippocampal GluR2/3- and calretinin-immunoreactive hilar neurons (presumptive mossy cells) in two mouse models of temporal lobe epilepsy

Abstract: Summary Purpose:  Hippocampal mossy cells receive dense innervation from dentate granule cells and, in turn, mossy cells innervate both granule cells and interneurons. Mossy cell loss is thought to trigger granule cell mossy fiber sprouting, which may affect granule cell excitability. The aim of this study was to quantify mossy cell loss in two animal models of temporal lobe epilepsy, and determine whether there exists a relationship between mossy cell loss, mossy fiber sprouting, and granule cell dispersion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
33
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 68 publications
(143 reference statements)
7
33
1
Order By: Relevance
“…We found that MC excitation in the ipsilateral hemisphere also prevented seizure generalization (Fig. 3, C and D), despite the greater degree of hippocampal sclerosis ipsilaterally, where we observed a 77% MC loss compared with a 55% MC loss contralaterally, consistent with previous studies (9) (fig. S15).…”
supporting
confidence: 92%
See 2 more Smart Citations
“…We found that MC excitation in the ipsilateral hemisphere also prevented seizure generalization (Fig. 3, C and D), despite the greater degree of hippocampal sclerosis ipsilaterally, where we observed a 77% MC loss compared with a 55% MC loss contralaterally, consistent with previous studies (9) (fig. S15).…”
supporting
confidence: 92%
“…We first tested how MC activity affects spontaneous electrographic, nonconvulsive seizures in a well-established model of TLE with kainic acid (KA) injected unilaterally into the left dorsal hippocampus (8, 9). We used a closed-loop seizure detection and intervention method in chronically epileptic mice (10) to deliver a 15-s light pulse at the onset of 50% of detected seizures (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of cells counted was multiplied by 68.6 (1/12 for sections analyzed; 1 ⁄ 4 counting area and 70/100 tissue shrink factor (29). In all cases optimum sampling was achieved as the coefficient of error (CE) is lower than the coefficient of variation (30). The doublecortin-positive cells were categorized into the mitotic and post mitotic types as previously described by Plümpe et al (31).…”
Section: Methodsmentioning
confidence: 99%
“…Our findings on the MCs of the CFLP strain are in sharp contrast with the general and widely accepted concept that the MCs are highly vulnerable to glutamate-mediated seizures. SE induced by convulsants such as PILO (Silva and Mello 2000) and kainate (Volz et al 2011) led to a loss of MCs. However, in two other mouse strains (Balb/c and NMRI) lacking documented common ancestors (Beck et al 2000) with the CFLP strain, we also found dramatic and different reductions in the density of the MCs after PILO treatment (Dobó et al 2015).…”
Section: Mouse Mossy Cellsmentioning
confidence: 98%